Critical Analyses of Educational Reforms in an Era of Transnational Governance (Educational Governance Research,, 2018)
This book represents a set of critical analyses of educational reforms where issues of transnational governance are of vital concern. It focuses on different aspects of, and practices in educational reform-making, and in particular on governing techniques and the working of new agencies such as supranational and multinational organizations. In addition, the book examines contemporary issues of immigration/immigrants in the politics of schooling, by reflecting on matters of migration, and problematizing how concepts such as exclusion and abjection make the migrants appear "failed", "insufficient" and even "dangerous". The book provides theoretical insights into critical relations between knowledge and power, governance and governmentality, and notions concerning educational systems, as well as how these are compared. The central themes of the book are models for organizing and reflecting on transnationalization and educational reforms. In its discussion of those themes, the focus lies on changing conceptions of education and the educational system; on how school or teacher education is adapting to discourses of effectiveness and efficiency; and on their transformation according to standardized templates. Such changing conceptions define the meanings of education and educational progress; they are important for the identification and analysis of educational knowledge, and for critical discourses on education in society. .